1995
DOI: 10.1111/j.1600-079x.1995.tb00137.x
|View full text |Cite
|
Sign up to set email alerts
|

The pineal gland of the aging rat: Calcium localization and variation in the number of pinealocytes

Abstract: In the present study, we investigated the population of pinealocytes in the pineal gland of aging rats. Dark and light pinealocytes were analyzed as to their calcium content. Calcium localization was realized in dark and light cells by means of cytochemistry and X-ray microanalysis. Calcium was mainly localized in dark pinealocytes characterized by many ultrastructural signs of degeneration. The number of pinealocytes per square surface of aged rats (28 months) was compared to young ones (3-4 months). While th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 51 publications
(33 reference statements)
1
7
0
2
Order By: Relevance
“…Schmid (1993) summarized evidence, further confirmed by Humbert and Pevet (1995), that calcification of pinealocytes results from death or degeneration of the cell itself, thus leading to an overall decrease in pineal activity. Besides, it has been shown that, with age, there is a significant reduction in both melatonin content and the total number of pinealocytes due to a reduction of light pinealocytes, which are known to be functional (Skene et al 1990;Humbert and Pevet 1995). Occurring simultaneously, there is an increase of dark pinealocytes, which are characterized by an intranuclear deposition of calcium and with many signs of degeneration (Schmid et al 1994;Humbert and Pevet 1995).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Schmid (1993) summarized evidence, further confirmed by Humbert and Pevet (1995), that calcification of pinealocytes results from death or degeneration of the cell itself, thus leading to an overall decrease in pineal activity. Besides, it has been shown that, with age, there is a significant reduction in both melatonin content and the total number of pinealocytes due to a reduction of light pinealocytes, which are known to be functional (Skene et al 1990;Humbert and Pevet 1995). Occurring simultaneously, there is an increase of dark pinealocytes, which are characterized by an intranuclear deposition of calcium and with many signs of degeneration (Schmid et al 1994;Humbert and Pevet 1995).…”
Section: Discussionmentioning
confidence: 89%
“…Besides, it has been shown that, with age, there is a significant reduction in both melatonin content and the total number of pinealocytes due to a reduction of light pinealocytes, which are known to be functional (Skene et al 1990;Humbert and Pevet 1995). Occurring simultaneously, there is an increase of dark pinealocytes, which are characterized by an intranuclear deposition of calcium and with many signs of degeneration (Schmid et al 1994;Humbert and Pevet 1995). With the present data, we may be able to add a link missing so far in the chain of arguments that an increased calcification of the pineal gland represents a decrease in the number of functioning pinealocytes, which results in a decreased ability of the pineal gland to produce melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested elsewhere [6], reduced activity of the arylalkylamine N -acetyltransferase, linked to an impaired pineal catecholaminergic neurotransmission, could result in diminished or suppressed nocturnal production. Moreover, the aging process leads to pineal gland calcification [35], [36]. Our investigations (unpublished) have shown modifications at the level of the pinealocytes and an accumulation of calcium deposits in both the pineal organ and retina of aged shrews compared to young individuals.…”
Section: Discussionmentioning
confidence: 90%
“…Light and dark pinealocytes have also been distinguished in many species, e.g. mouse (Upson et aI., 1976), rat (Johnson, 1980;MiJin et aI., 1990;Humbert and Pevet, 1995), horse (Cozzi, 1986), rabbit (Krakowski and Cieciura 1992), gerbil (Redecker, 1993) and pig (Przybylska, 1989;Lewczuk et al, 1994). However, the nature of the two forms of cells was controversial.…”
Section: Introductionmentioning
confidence: 99%